2015
DOI: 10.1002/hep.27795
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐on‐chronic liver failure precipitated by hepatic injury is distinct from that precipitated by extrahepatic insults

Abstract: Patients with acute-on-chronic liver failure (ACLF) represent a heterogeneous population. The aim of the study is to identify distinct groups according to the etiologies of precipitating events. A total of 405 ACLF patients were identified from 1,361 patients with cirrhosis with acute decompensation and categorized according to the types of acute insults. Clinical characteristics and prognosis between the hepatic group and extrahepatic group were compared, and the performance of prognostic models was tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
259
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(287 citation statements)
references
References 33 publications
13
259
1
5
Order By: Relevance
“…In contrast, a Chinese study showed comparable 28-day mortality (50.7% vs. 48.3%, P = 0.22) but increased 90-day mortality in extrahepatic ACLF than hepatic ACLF group (68.3% vs. 58.9%, P = 0.035). 17 This difference could be explained by the fact that the majority of hepatic ACLF in the Chinese study was due to HBV flare on underlying HBV cirrhosis, which is an imminently treatable condition by use of potent antivirals, unlike severe alcoholic hepatitis, which was the most common cause of hepatic ACLF in our study. Hence, 90-day mortality in hepatic ACLF group was high in our study compared to the previous study, and we did not find any difference in mortality between hepatic and extrahepatic ACLF.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In contrast, a Chinese study showed comparable 28-day mortality (50.7% vs. 48.3%, P = 0.22) but increased 90-day mortality in extrahepatic ACLF than hepatic ACLF group (68.3% vs. 58.9%, P = 0.035). 17 This difference could be explained by the fact that the majority of hepatic ACLF in the Chinese study was due to HBV flare on underlying HBV cirrhosis, which is an imminently treatable condition by use of potent antivirals, unlike severe alcoholic hepatitis, which was the most common cause of hepatic ACLF in our study. Hence, 90-day mortality in hepatic ACLF group was high in our study compared to the previous study, and we did not find any difference in mortality between hepatic and extrahepatic ACLF.…”
Section: Discussionmentioning
confidence: 55%
“…This is in contrast to studies from East Asia where hepatitis B is the predominant cause of chronic liver disease as well as acute insult in patients with ACLF. 17 Patients with hepatic ACLF had higher bilirubin values and higher proportion of liver failure when compared to extrahepatic ACLF. In addition, hepatic ACLF group had higher MELD and CLIF-SOFA score at admission.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, Xun et al (8) reported that the integrated MELD (iMELD) and MELD with incorporation of sodium (MELD-Na) models predicted 3-month mortality rates more accurately than traditional MELD. Furthermore, Shi et al (9) demonstrated that iMELD predicted hepatic-ACLF more accurately when compared with various other scoring systems (9). However, the prognostic assessment of ACLF in patients with multiple organ failure remains to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, extrahepatic insults can be linked to a different outcome [7] . A potential precipitating event of the syndrome may not be identifiable [3] .…”
Section: Introductionmentioning
confidence: 99%